Identification of Factors Contributing to Primary Female Subfertility by Diagnostic Hystero-Laparoscopy: An Experience of Private Hospital - Yousaf Latif Khan; Sajida Imran; Zahra Samreen (Journal of Shalamar Medical & Dental College, 2022)
Background: Management of subfertility is influenced by the diagnosis of its causative factor. Combined diagnostic hystero-laparoscopy has emerged as an effective procedure in identifying causative factors of female subfertility.